Fact and fiction - Russell, Bertrand; Tankarvi, Muhammed Iqbal ([Bharuch : Darul Uloom Matliwala], 1961)
With reference to India.
Includes bibliographical references.
Rashid
Keywords: Islamic religious education -- India; Fact and fiction; Islamic religious education -- Study and teaching -- India; Madrasahs -- India